Sovereign credit rating mismatches - Afonso, António (2017)
We study the factors behind split ratings in sovereign credit ratings from different agencies, for the period 1980-2015. We employ random effects ordered and simple probit approaches to assess the explanatory power of different macroeconomic, government and financial variables. Our results show that structural balances and the existence of a default in the last ten years were the least significant variables whereas the level of net debt, budget balances, GDP per capita and the existence of a default in the last five years were found to be the most relevant variables explaining rating mismatches across agencies. For speculative-grade ratings, we also find that a default in the last two or five years decreases the rating difference between S&P and Fitch. For the positive rating difference between S&P and Moody’s for investment-grade ratings, an increase in external debt leads to a smaller rating gap between the two agencies